2004
DOI: 10.1021/tx0498206
|View full text |Cite
|
Sign up to set email alerts
|

Guanine−Adenine DNA Cross-Linking by 1,2,3,4-Diepoxybutane:  Potential Basis for Biological Activity

Abstract: 1,2,3,4-Diepoxybutane (DEB) is a prominent carcinogenic metabolite of 1,3-butadiene (1,3-BD), an important industrial chemical and an environmental pollutant found in cigarette smoke and automobile exhaust. DEB is capable of inducing a variety of genotoxic effects, including point mutations, large deletions, and chromosomal aberrations. The mutagenicity and carcinogenicity of DEB are thought to result from its ability to form bifunctional DNA-DNA adducts by sequentially alkylating two nucleobases within the DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
66
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(72 citation statements)
references
References 31 publications
6
66
0
Order By: Relevance
“…Meso-DEB, unlabeled N7G-N1A-BD, N7G-N3A-BD, N7G-N7A-BD, and N7G-N 6 A-BD were synthesized as previously reported (39). 15 2′-Deoxyadenosine (49.7 mg), 15 N 3 , 13 C 1 -dG (8.8 mg), and glacial acetic acid (1 mL) were combined in a microcentrifuge tube and heated to 80 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meso-DEB, unlabeled N7G-N1A-BD, N7G-N3A-BD, N7G-N7A-BD, and N7G-N 6 A-BD were synthesized as previously reported (39). 15 2′-Deoxyadenosine (49.7 mg), 15 N 3 , 13 C 1 -dG (8.8 mg), and glacial acetic acid (1 mL) were combined in a microcentrifuge tube and heated to 80 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Among these, N7G-N3A-BD and N7G-N7A-BD are thermally labile and can be spontaneously released from the DNA backbone under physiological conditions, while N7G-N1A-BD and N7G-N 6 A-BD require acid hydrolysis to undergo depurination (39). In the present work, we report an HPLC-ESI + -MS/MS method for sensitive and accurate quantitation of adenine-guanine cross-links of DEB in vitro and in vivo and its application to analyses of guanine-adenine (G-A) BD cross-links in liver DNA of BD-exposed and control female B6C3F1 mice.…”
Section: Introductionmentioning
confidence: 99%
“…1720 DNA adducts induced by BD exposure include N-7-(2-hydroxy-3-buten-1-yl)guanine, N-7-(1-hydroxy-3-buten-2-yl)guanine, N-7-(2,3,4-trihydroxy-3-buten-2-yl)guanine, 21 1,4- bis -(guan-7-yl)-2,3,-butanediol ( bis -N7G-BD), 22,23 1-(guan-7-yl)-4-(aden-1-yl)-2,3-butanediol (N7G-N1A-BD), 1-(guan-7-yl)-4-(aden-3-yl)-2,3-butanediol(N7G-N3A-BD), and 1-(guan-7-yl)-4-(aden-7-yl)-2,3-butanediol (N7G-N7A-BD). 22 Several BD-induced hemoglobin adducts have been identified, e.g. N -(2-hydroxy-3-buten-1-yl)-valine (HB-Val), 1,2,3-trihydroxybutyl-valine (THB-Val), and N,N -(2,3-dihydroxy-1,4-butadiyl)-valine (Pyr-Val).…”
Section: Introductionmentioning
confidence: 99%
“…[14] However, Guenthner et al have reported that DNA adducts of 2 can be formed in vitro but were not detectable in vivo. [9,15] The structure of 2 is similar to that of many epoxides whose genotoxicity and potential formation of DNA adducts have been well studied, [16][17][18] which led to our interest in purifying and characterizing potential DNA adducts of 2 in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20] For example, allylbenzene 2Ј,3Ј-oxide has been shown to react with 2Ј-deoxyguanosine to form N 2 -(2Ј-hydroxy-3Ј-phenylpropyl)-2Ј-deoxyguanosine. [9] In order to gain more insight into the genotoxicity of 2, we needed to synthesize related DNA adducts as standards.…”
Section: Introductionmentioning
confidence: 99%